Basic Profile of Child Marriage in Pakistan - Malé, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Pakistan. Measures of child marriage remain substantial. The share of women ages 18-22 who married as children is 18.7 percent, but it has declined substantially over time. The share of girls marrying very early, before the age of 15, has also declined. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.